Strafbaar Feit as a Reason for Impeachment of The President - Yulida, Devi; Anggreini, Rini; Nurmalawaty (Mahadi: Indonesia Journal of Law, 2024)
One of the legal reform agendas in Indonesia is to strengthen the presidential government system by clearly and firmly regulating the reasons for impeachment in the constitution. Article 7A of the 1945 Constitution of the Republic of Indonesia explains that the President and/or Vice President can be impeached for serious offenses such as treason, corruption, bribery, disgraceful acts, and other serious crimes. Considering the extensive powers of the President, it is important to analyze criminal acts further as reasons for impeachment. This research uses a normative juridical approach with descriptive-analytical analysis. Data collection methods are conducted through library research with primary data sources in the form of laws and secondary sources in the form of relevant literature. The research results show that the impeachment mechanism in Indonesia involves the Constitutional Court in assessing the House of Representatives 's accusations against the President, ensuring that impeachment is based on political and legal decisions. Additionally, criminal acts committed by the President can still be pursued in general courts for legal accountability. This aligns with the rule of law principle that ensures everyone is subject to the law without exception. Adjustments by state institutions involved in the impeachment procedure are expected to clarify the implementation of impeachment in Indonesia.